2020
DOI: 10.1111/ajt.15845
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically modifying the Foxp3 locus for generation of stable antigen-specific Tregs as cellular therapeutics

Abstract: Foxp3+ regulatory T cells (Tregs) are potent immunoregulatory cells, prompting strong interests in manipulating them for therapeutic purposes. However, significant challenges remain, including their heterogeneity and functional instability. Here we focused on the inducible Tregs (iTregs) and studied whether the Foxp3 locus can be epigenetically edited ex vivo to produce stable therapeutic iTregs. Under iTreg‐inducing condition where activated CD4+ T effector cells were converted to Foxp3+ Tregs, we tested appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This is because T effectors may acquire transient Foxp3 expression upon activation [63]. Considering the Tregs populations, nTregs acquire stable and profound TSDR demethylation, while iTregs remain almost completely methylated, which makes them less stable during cell culture [64]. In addition, Tregs that are generated in vivo have similar, albeit lower TSDR demethylation compared to nTregs [65].…”
Section: Foxp3 Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because T effectors may acquire transient Foxp3 expression upon activation [63]. Considering the Tregs populations, nTregs acquire stable and profound TSDR demethylation, while iTregs remain almost completely methylated, which makes them less stable during cell culture [64]. In addition, Tregs that are generated in vivo have similar, albeit lower TSDR demethylation compared to nTregs [65].…”
Section: Foxp3 Dna Methylationmentioning
confidence: 99%
“…The research conducted on mice has shown a beneficial effect of stimulated iTregs on the prevention of GvHD or allograft rejection [86,87]. More complex research on iTregs, including the cooperation of three epigenetic modifiers, including vitamin C, has disclosed a deep CNS2 demethylation in stimulated cells with high stability and usefulness in therapeutic trials [64].…”
Section: Epigenetic Modifiers Of the Foxp3 Locusmentioning
confidence: 99%
“…Independent of the known anticancer effects of HDACi, such as proapoptotic activity or cell cycle arrest induction 18 , the anti-inflammatory functions of these agents have recently aroused interest 19 . Previous researches have showed that epigenetic regulation play roles in Treg stability 20 ; for example, the HDACi trichostatin A (TSA) prevented the differentiation of human Foxp3 + Tregs into IL-17 producing cells 21 . Among the multiple HDACs Treg expresses, HDAC9 was proved to play an important role in regulating Foxp3-dependent suppression 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that V-iTregs prolonged skin allograft survival to a greater extent than did C-iTregs, which is consistent with their better in vitro suppressive activity. However, these studies had induced V-iTregs with vitamin C together with vitamin A or sodium butyrate [19,27]. On the other hand, systemic administration of vitamin C alone did not improve skin allograft survival in vitamin C-sufficient RAG KO mice, although vitamin C increased generation of iTregs and Foxp3 levels [25].…”
Section: Plos Onementioning
confidence: 99%
“…A limitation associated with the current study was that we did not combine vitamin C with other agents, such as vitamin A and histone modifiers, for stabilization of Foxp3 in iTregs to boost the beneficial effects of vitamin C on iTregs [16,27,29,30]. P2X7 receptor blockade suppressed effector T cells or induced Tregs, thereby suppressing ischemia-reperfusion injury and allograft rejection [31,32].…”
Section: Plos Onementioning
confidence: 99%